PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, MINAT BELAJAR, DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA AKUNTANSI DI UNIVERSITAS TRIATMA MULYA - Desiana Wahyu Wedayanthi Rahayu; I Ketut Yudana Adi (Journal Research of Accounting, 2023)
At present, with the rapid development of financial institutions and banks, the demand for accounting graduates is also increasing. The truth, however, is that a large number of graduates are produced in higher education, but only a small fraction are absorbed into the workforce. This phenomenon shows that the level of understanding becomes very important. Comprehension of student accounting is indicated by the student's understanding of the material being studied. The factors that promote understanding are emotional intelligence, intelligence, interest in learning, and learning behavior. The purpose of this study was to examine the effects of emotional intelligence, intelligence, interest in learning, and learning behavior on the level of accounting comprehension. The study used a sample of 66 accounting students from Triatma Mulya University. In this study, multiple linear regression analysis was used as the data analysis technique. The results show that emotional intelligence, intellectual intelligence, learning interest and learning behavior have a positive and significant impact on accounting comprehension. This means that the more emotional intelligence, IQ, interest in learning and learning behavior a person has, the more knowledge related to accounting they will know.